REINTERPRETASI JIHAD MELALUI ASPEK HISTORIS-KULTURAL SEBAGAI UPAYA MERUMUSKAN ISLAM RAHMAT SEMESTA ALAM - Ach. Muhyiddin Khotib (Al'Adalah, 2015)
Islam not present in a vacuum culture .Grounded in the teachings of civilizations and certain culture. This process it requires an understanding of the teachings of islam without release from the roots of cultural history. One of the nucleus in islam is about “Jihad”. Laterly, interpretation about Jihad of-ten identified with physical war destructive violent. This is caused by con-duct a few moslems lately who performs acts of terrorism and namely his actions with “jihad”. Give Understanding Jihad with war or give priority to meaning that war in the training Jihad contradictory with the mission muslim mercy of the universe. So, Jihad should be interpreted back within the cultural-histories framework of the holy teaching was not unsullied by the understanding that generated jihad throughout the space and certain culture. A teaching about jihad to read in accordance with the culture at that time and should be adapted to the context of the days when and where that is grounded. Reasonable, if the war to the primary meaning because the culture of the arab are conflicts intense that always to put forward physical contact (war) to resolve the conflict. This culture is not always the same with the other culture, thus the meaning of war is at meaning subordinate.